(3OjhGf TYQs
(3ChdgG (B:s
(3NdhJ Hg Yf cd Yjf QbjHI Shi GdOgQ jZfj Yf Yjhf GdZhGeQ hjdjgG hbGd CjVkG(B: (3YTbrJ bOg YUhf GdBS eG JQi eG HgG ef GdhShGS s
(3BNQgG (B:s
(3Je GdOjhGf GdeHGQc s
(3de ojTQ GdeDda Edi GdZQV ef Cj bUjOI aj cd GdOjhGfs
(3hgh ZjQ eQJH Ydi GdMQhas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B134 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs